Building Supracolloidal Fibers from Zwitterion‐Stabilized Adhesive Emulsions. (19th September 2018) - Santa Chalarca, Cristiam F.; Letteri, Rachel A.; Perazzo, Antonio; Stone, Howard A.; Emrick, Todd
Abstract: Oil‐in‐water droplets stabilized with polymer zwitterions (PZWs) exhibit salt‐responsive aggregation–disaggregation behavior. Here, a method to shape these droplets is described, starting from their aggregated state, into supracolloidal fibers by simply extruding them into aqueous media. The effect of salt concentration, in both the initial emulsion and the aqueous medium, on the ability of the emulsions to form fibers is examined. After fiber formation, a transition from well‐defined macroscopic structures to noninteracting droplet dispersions can be triggered, simply by increasing the salt concentration of the aqueous environment. The interdroplet energy of adhesion and emulsion rheology correlate qualitatively with salt concentration and thus impact the ability of the emulsions to be shaped by extrusion. The interdroplet adhesion is dependent on both salt concentration and polymer composition, which allows tailoring of conditions to trigger fiber disaggregation. Finally, fibers with variable compositions along their length are prepared by sequential loading and extrusion of emulsions containing oil phases of differing densities. Abstract : All‐liquid macroscopic supracolloidal fibers are fabricated using droplets as building blocks. Polymer zwitterion surfactants endow oil‐in‐water emulsions with tailorable interdroplet adhesion. Extrusion of emulsion networks affords robust, macroscopic fibers, the disaggregation of which is triggered by salt. This functional droplet platform also allows for the fabrication of supracolloidal fibers of variable chemical composition along their length.